Efficiency Analysis of Islamic Banks Post-Merger Using DEA Methods - Orieza Alif Putra Purnomo; Tika Arundina Aswin (International Journal of Economics Development Research (IJEDR), 2024)
This academic study explores the impact of mergers on the efficiency of Islamic banks in Indonesia, mainly focusing on Bank Syariah Indonesia (BSI), formed from the merger of three state-owned Islamic banks. Covering the period from 2017 to 2023, the research utilizes Data Envelopment Analysis (DEA) to assess efficiency levels before and after the merger. Secondary data from financial statements and regulatory reports are analyzed to determine changes in market concentration and performance metrics such as profitability and operational efficiency. Results indicate a general decline in the industry’s average efficiency post-merger despite BSI itself showing improvements in operational metrics. This study contributes to understanding the complex effects of mergers in the Islamic banking sector, offering insights for policymakers and stakeholders into the dynamics of corporate restructuring within the industry.